PENGARUH PENEMPATAN, MOTIVASI KERJA, DAN STRES KERJA TERHADAP KEPUASAN KERJA - Angga Dwipalguna, A.A Ngr; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
The purpose of this study was to examine the effect of the placement, motivation and work stress either simultaneously or partially on employee satisfaction Department of Industry and Trade of Denpasar, and variables dominant influence on job satisfaction. The study population is employees of the Department of Industry and Trade of Denpasar as many as 47 people. Data was collected by questionnaire. The analysis technique used is multiple linear regressions. The study states the variable placement, motivation, a positive contribution to job satisfaction and job stress contributes negatively to job satisfaction. Partial assay results indicate that the placement and work motivation partially influence on job satisfaction. Work stress contributes negatively to job satisfaction. Farsial test showed that placement, motivation and stress simultaneously affect the job satisfaction.
Keywords: Placement, Work Motivation, Job Stress and Job Satisfaction